Use of guided inquiry learning model to improve skills of biological science process to senior high school students - Noor Lailah Sahlan (Badan Pengembangan Sumber Daya Manusia Provinsi DKI Jakarta, 2019)
The purpose of this study is to determine the extent to which students 'science process skills in Biology subjects can be increased through the use of Guided Inquiry learning models and to know students' responses to learning that has been implemented as a reflection of learning. This research was conducted at SMAN 1 Kota Tangerang Selatan on students of class XII Science. This research uses Classroom Action Research (CAR) methods. The results showed that the use of Guided Inquiry learning models in Biology concepts of plant growth and development concepts can provide positive and significant improvements to students' science process skills.